Reduction of in vitro viral replication of caprine alphaherpesvirus 1 (CPHV-1) through natural antiviral treatment with plant extracts = Reducción de la replicación viral in vitro de alfaherpesvirus caprino 1 (CpHV-1) por tratamiento antiviral natural de extractos de plantas - Ferreccio, Carola Maria; Maidana, Silvina Soledad; Tau, Rocio Lucia; Di Ciaccio, Lucia Soledad; Spotorno, Viviana Graciela; Salvat, Adriana Elisabeth; Aguilar, Juan Javier; Konigheim, Brenda; Romera, Sonia Alejandra (Facultad de Ciencias Veterinarias, Universidad Nacional del Nordeste, 2025)
Caprine herpesvirus 1 (CpHV-1) is distributed worldwide, causing significant economic losses. The application of acyclovir interferes with viral replication to varying degrees of efficacy, but it does not prevent the establishment of latency. Due to the costs and side effects associated with synthetic drugs, the search for new chemotherapeutic agents is essential for the treatment and control of viral diseases. The objective of this study is to evaluate and compare the in vitro antiviral activity of three native plants from Argentina as a therapeutic antiviral treatment against CpHV-1. Larrea divaricata, Minthostachys verticillata and Parastrephia quadrangularis were used. Four parameters were analyzed: Cytotoxic Concentration 50 (CC50), Inhibitory Concentration 50 (IC50), quantification by plaque assay and viral titration. The L. divaricata extract showed the lowest cytotoxicity (2.4 mg ml-1). The best selectivity index (SI) was obtained with the M. verticillata extract (10). L. divaricata and P. quadrangularis extracts demonstrated the greatest antiviral effects, with reductions of 90% and 75%, respectively, compared to untreated controls, where the greatest reduction in plaque size was observed. The highest inhibition of viral replication observed in the viral titration quantification occurred when monolayers were treated with L. divaricata, resulting in at least a 35% reduction. The combination of assay with L. divaricata and M. verticillata showed the greatest reduction in viral titers. The overall results provide evidence that L. divaricata and M. verticillata could serve as potential sources for new anti-CpHV-1 drugs.